2022
DOI: 10.1371/journal.ppat.1010892
|View full text |Cite
|
Sign up to set email alerts
|

Requirement of a functional ion channel for Sindbis virus glycoprotein transport, CPV-II formation, and efficient virus budding

Abstract: Many viruses encode ion channel proteins that oligomerize to form hydrophilic pores in membranes of virus-infected cells and the viral membrane in some enveloped viruses. Alphavirus 6K, human immunodeficiency virus type 1 Vpu (HIV-Vpu), influenza A virus M2 (IAV-M2), and hepatitis C virus P7 (HCV-P7) are transmembrane ion channel proteins that play essential roles in virus assembly, budding, and entry. While the oligomeric structures and mechanisms of ion channel activity are well-established for M2 and P7, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 114 publications
3
8
0
Order By: Relevance
“…This may be due to that the deletion of the 6K protein leads to occurance of abnormal posttranslational modification on some precursor proteins. The similar case has been shown in Elmasri et al's research 30 …”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…This may be due to that the deletion of the 6K protein leads to occurance of abnormal posttranslational modification on some precursor proteins. The similar case has been shown in Elmasri et al's research 30 …”
Section: Discussionsupporting
confidence: 88%
“…These results showed that the process of E2 protein transport from the Golgi apparatus to the plasma membrane was inhibited after the deletion of 6K protein, thereby affecting the subsequent processing of viral particles and resulting in a decrease in the release of viral particles (Figure 5). It has recently been found that ion channel activity of SINV 6K protein is necessary for facilitating glycoprotein spike transport to plasma membrane and effective viral budding 30 . Similarly, our experimental results also indicate that the defect in transportation glycoprotein E2 to the cell membrane is caused by the deletion of the 6K protein.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Assembly of CHIKV is driven by the interaction of capsid protein and the cytoplasmic tail of the E2 protein (47). However, recent studies suggest that accessory proteins 6k and TF may also facilitate efficient exit of Sindbis virus, a closely related alphavirus (8).…”
Section: Introductionmentioning
confidence: 99%